2009
DOI: 10.1073/pnas.0810869106
|View full text |Cite
|
Sign up to set email alerts
|

Fe65 is required for Tip60-directed histone H4 acetylation at DNA strand breaks

Abstract: Fe65 is a binding partner of the Alzheimer's ␤-amyloid precursor protein APP. The possible involvement of this protein in the cellular response to DNA damage was suggested by the observation that Fe65 null mice are more sensitive to genotoxic stress than WT counterpart. Fe65 associated with chromatin under basal conditions and its involvement in DNA damage repair requires this association. A known partner of Fe65 is the histone acetyltransferase Tip60. Considering the crucial role of Tip60 in DNA repair, we ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 35 publications
1
55
0
Order By: Relevance
“…2). Of course, Fe65 suppression leads to reduced phosphorylation of H2AX and decreased efficiency of DNA repair (52). The crucial involvement of APP in this machinery is supported by the observation that APP/APLP2 knockdown has the same effects observed with Fe65 suppression, that is, reduced recruitment of Tip60 at DNA breaks and reduced histone H4 acetylation (52).…”
Section: )mentioning
confidence: 91%
See 2 more Smart Citations
“…2). Of course, Fe65 suppression leads to reduced phosphorylation of H2AX and decreased efficiency of DNA repair (52). The crucial involvement of APP in this machinery is supported by the observation that APP/APLP2 knockdown has the same effects observed with Fe65 suppression, that is, reduced recruitment of Tip60 at DNA breaks and reduced histone H4 acetylation (52).…”
Section: )mentioning
confidence: 91%
“…A first set of experiments demonstrated that the Fe65 knockdown hampers the recruitment of Tip60 at DNA strand breaks and in turn the acetylation of histone H4 (52). This event could explain the defects in the DNA damage response and in the DNA repair observed as a consequence of Fe65 suppression.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports also showed that FE65 involved in the response of cell stress, especially to DNA damages [88,96]. FE65 and APP have also been shown to regulate neuronal membrane motility by interacting with Mena, a regulator of actin dynamics that is important for neurite growth and synapse modification [90,91]. The physiological roles of the FE65…”
Section: Fe65 Family Of Proteinsmentioning
confidence: 99%
“…The present knowledge for FE65 function includes a role for FE65 in DNA repair, especially following DNA double strand breaks (Minopoli et al, 2007;Stante et al, 2009). However, the molecular mechanism is unknown.…”
Section: Fe65 Mediates Cell Cycle Re-entry In Ad 2487mentioning
confidence: 99%